2017
DOI: 10.1590/0103-6440201700933
|View full text |Cite
|
Sign up to set email alerts
|

Association between Root Caries and Depressive Symptoms among Elders in Carlos Barbosa, RS, Brazil

Abstract: The aim of this study was to evaluate the association between depressive symptoms and root caries among independent-living older persons. All community-dwelling older adults (not hospitalized and not bedridden) living in Carlos Barbosa, RS, Brazil, were invited to participate, and 785 completed the study protocol (standardized questionnaire assessing socio-demographic information and health behavior, Geriatric Depression Scale [GDS] -brief version, and oral examination [DMFT-Root index, Visible Plaque Index an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Most of them were conducted in Asia (n = 20, China [11][12][13][14][15][16], India [17][18][19][20][21][22][23][24], Singapore [25], Turkey [26][27][28][29][30][31][32][33][34][35][36][37][38] and Vietnam [29,30]) and Europe (n = 10, Finland [31], Germany [32,33], Ireland [34], Kosovo [35], Norway [36], Poland [37,38], Portugal [39] and Romania [40]). There were three studies conducted in North America (Mexico [41,42] and USA [43]), one in South America (Brazil [44]), two in Oceania (Australia [45,46]) and three in Africa (Egypt [47], Malawi [48] and South Africa…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of them were conducted in Asia (n = 20, China [11][12][13][14][15][16], India [17][18][19][20][21][22][23][24], Singapore [25], Turkey [26][27][28][29][30][31][32][33][34][35][36][37][38] and Vietnam [29,30]) and Europe (n = 10, Finland [31], Germany [32,33], Ireland [34], Kosovo [35], Norway [36], Poland [37,38], Portugal [39] and Romania [40]). There were three studies conducted in North America (Mexico [41,42] and USA [43]), one in South America (Brazil [44]), two in Oceania (Australia [45,46]) and three in Africa (Egypt [47], Malawi [48] and South Africa…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, eight studies investigated the association between plaque control and caries. Six studies revealed that reduced toothbrushing frequency to once per day [11,17,36], twice per week [44] or no toothbrushing at all [39,47] increased the risk. A systematic review found similar results that people who brushed their teeth infrequently were at higher risk for incidence of new caries than those who brushed frequently [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation